A comparison in precision and accuracy of the conventional syringe to the Suh precision syringe - DeLuna D (Dove Medical Press, 2019)
Devin DeLuna,1 Audrey Netzel,2 Jamie Dietze,1 Brett A Begley,1 Jideofor K Ndulue,1 Donny W Suh1 1Department of Ophthalmology, University of Nebraska Medical Center, Omaha, NE, USA; 2Department of Ophthalmology, Creighton University School of Medicine, Omaha, NE, USACorrespondence: Audrey NetzelDepartment of Ophthalmology, Creighton University School of Medicine, 626 N 41st Street, Omaha, NE 68131, USATel +1 608 214 7857Email audreynetzel@creighton.eduPurpose: To compare the accuracy and precision of a conventional intraocular syringe to the Suh precision syringe (SPS), a new injection device designed to decrease operator error and to reduce adverse outcomes by providing a more ergonomic technique for periocular and intraocular injections.Methods: Participants were instructed to inject a specified quantity of water into a 0.2 mL polymerase chain reaction (PCR) tube and a sheep eye, first with the conventional syringe, and then with the SPS. The degree of needle movement during injection was video recorded and analyzed for forward-retraction movement and variability in movement. The volume of water injected into the PCR tube was also documented. Data was analyzed using a Wilcoxon signed-rank test.Results: As compared to the conventional syringe, the SPS had significantly less forward-retraction movement when injecting into the sheep eye (P=0.04). Similarly, the forward-retraction movement of the needle when injecting into the PCR tube was less while using the SPS compared with the conventional syringe; however, this was not statistically significant (P=0.09). There was no significant difference in the volume of water expelled from both syringes (P=0.28).Conclusion: The SPS demonstrates significant potential to decrease the overall risk involved with injections through reduction of forward-retraction movement during device operation. This new syringe design also provides better control with injection depth and drug injection volume. With its more ergonomic design, the SPS has the potential to decrease risks associated with intraocular injections by improving the accuracy and precision of the injection.Keywords: Suh precision syringe, intraocular injection